Effects of Aerobic Exercises on Postmenopausal Depression: Randomized Controlled Trial - Nadia Bashir, Zainab Hassan, Zaryyab, Masooma Saleem, Malik Muhammad Atif, Zunaira Mehdi, (Pakistan Journal of Medical & Health Sciences, 2023)
Menopause, is a stage in female life where there is a permanent stoppage of female menstrual cycle because of gonadal steroidal loss and oocyte depletion. A perimenopause state is characterized by gradual oocytes loss, widespread hormonal fluctuations and irregular menses cycle. Aim: To determine the effects of aerobic exercises on post-menopausal women. Study design: Randomized controlled trial. Methodology: Study was completed during the time duration of six months. Simple convenient sampling technique was used among all females aged between 40-65 years. HDS was used for depression scoring. Normality of data was assessed by Kolmogorov test and the significance level showed that the data was normally distributed. Data was evaluated by using SPSS version 24. Descriptive statistical analysis was applied for the demographical data. Finally, the results for both control and interventional groups were computed via paired sample t-test and independent t-test respectively. Results: In this study, p=0.000 for MRS and P=0.000 for HDS in experimental group depicted that aerobic exercises are highly significant for treatment of depression if combined with the anti-depressant drugs therapy. Practical Implication: This study highlighted that use of aerobic exercises in combination with the drug therapy explored this mode of the treatment of the depression and other related symptoms among the post-menopausal women. Conclusion: It was concluded that the patients improve earlier if they were provided with the aerobic exercises along with the anti-depressant medications. Key words: Depression, Menopause Rating Scale, Postmenopausal and Hamilton rating scale for depression.